From “builders of rice fields” to labour migrations: noteworthy contributions by Philippe Sagant - Olivia Aubriot (Ateliers d'Anthropologie)
This brief note focuses on two aspects of Philippe Sagant’s work on the history of populations in Nepal: the conquest—which was above all technical—of the Indo-Nepalese as builders of rice fields; and the expansion of British capitalism to explain the first labour migrations abroad (in this case, to India).